SERS Detection of Dopamine Using Label-Free Acridine Red as Molecular Probe in Reduced Graphene Oxide/Silver Nanotriangle Sol Substrate - Luo, Yanghe (Nanoscale Res Lett, 2015)
The reduced graphene oxide/silver nanotriangle (rGO/AgNT) composite sol was prepared by the reduction of silver ions with sodium borohydride in the presence of H(2)O(2) and sodium citrate. In the nanosol substrate, the molecular probe of acridine red (AR) exhibited a weak surface-enhanced Raman scattering (SERS) peak at 1506 cm(−1) due to its interaction with the rGO of rGO/AgNT. Upon addition of dopamine (DA), the competitive adsorption between DA and AR with the rGO took place, and the AR molecules were adsorbed on the AgNT aggregates with a strong SERS peak at 1506 cm(−1) that caused the SERS peak increase. The increased SERS intensity is linear to the DA concentration in the range of 2.5–500 μmol/L. This new analytical system was investigated by SERS, fluorescence, absorption, transmission electron microscope (TEM), and scanning electron microscope (SEM) techniques, and a SERS quantitative analysis method for DA was established, using AR as a label-free molecular probe.